2020
DOI: 10.1021/acs.jpca.9b09879
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between σ Holes, Anion···H–C, and Cation−π Interactions in Dibromo[2,2]paracyclophane Complexes

Abstract: Theoretical calculations were performed to investigate the interplay between σ−hole, anion−HC and cation−π interactions in the complexes of dibromo[2,2]paracyclophane (DBr[2,2]PCP) with alkali (Li + , Na + , K + ), alkaline earth metal cations (Be 2+ , Mg 2+ , and Ca 2+ ), and halogen anions (F − , Cl − , and Br − ) using the wave function (MP2) and density functional theory (M06-2X and B3LYP) methods with the 6-311++G(d,p) basis set. The study reveals that DBr[2,2]PCP behaves as amphoteric molecule with a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The interaction of Li + , Na + , K + , Be 2 + , Mg 2 + , Ca 2 + , F À , and Cl À with dibromo[2.2]paracyclophane was studied theoretically by Muya et al. [8] These authors found that dibromo [2.2]paracyclophane could be a scavenger for trace cations and anions because it forms stable complexes with these ions via cation⋅⋅⋅π and anion⋅⋅⋅H À C interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of Li + , Na + , K + , Be 2 + , Mg 2 + , Ca 2 + , F À , and Cl À with dibromo[2.2]paracyclophane was studied theoretically by Muya et al. [8] These authors found that dibromo [2.2]paracyclophane could be a scavenger for trace cations and anions because it forms stable complexes with these ions via cation⋅⋅⋅π and anion⋅⋅⋅H À C interactions.…”
Section: Introductionmentioning
confidence: 99%